Topologically controlled phase transitions and nanoscale film self-assemblies of cage poly(ε-caprolactone) and its counterparts. Issue 5 (14th January 2021) - Ree, Brian J.; Mato, Yoshinobu; Xiang, Li; Kim, Jehan; Isono, Takuya; Satoh, Toshifumi
Abstract : Here we report the first quantitative investigation of nanoscale film morphologies of a cage-shaped poly( ε -caprolactone) and its counterparts in star, cyclic, and linear topologies through synchrotron grazing incidence X-ray scattering analysis. Abstract : Here we report the first quantitative investigation of nanoscale film morphologies of a cage-shaped poly( ε -caprolactone) ( cg -PCL9k ) and its counterparts in star, cyclic, and linear topologies ( st -PCL9k, cy -PCL6k, and l -PCL6k ) with consideration of topological influence through synchrotron grazing incidence X-ray scattering analysis. The folded crystalline layer thickness l c is found to be in the increasing order of: st -PCL9k < l -PCL6k < cy -PCL6k < cg -PCL9k . Additional structural parameters, such as lamellar orientation, crystallinity, and orientation of orthorhombic lattice in nanoscale film, exhibit intricate dependencies on their molecular topologies and steric influences from the molecular joints and end groups. Nevertheless, all topological PCLs form lamellar structures based on the orthorhombic crystal lattice in nanoscale films. In addition, crystallization temperature T c and crystal melting temperature T m of all PCLs in bulk are highly dependent on the molecular topology; both T c and T m follow the same increasing trend of: st -PCL9k < l -PCL6k < cy -PCL6k < cg -PCL9k . Phase transition characteristics such as heat of fusion and crystallinity in bulk state, and thermal stability also depend upon the topological and steric influences.